2016
DOI: 10.1016/j.jfbs.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Political connection and business transformation in family firms: Evidence from China

Abstract: A B S T R A C TWe investigate the impact of family ownership on core business transformation and the moderating role of political connections in this relation through a Probit model, conditional Logit model, and Heckman selection model with instrumental variable using data from Chinese listed companies covering 2001-2010. The results demonstrate that, compared with non-family firms, family firms are more likely to transform their core business, enter strongly correlative industries and non-regulated industries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…Entrepreneurial entry, in the context of an existing firm, is generally known as corporate entrepreneurship (CE). CE involves three main activities: Corporate venturing is the creation of organizations within or outside the existing organizational domain (Marchisio et al ); S trategic renewal is organizational renewal involving major strategic and/or structural changes (e.g., Wang et al ); and Innovation is the introduction of something new to the market (e.g., Block et al ). …”
Section: Conceptualizing Entrepreneurship In Family Firmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurial entry, in the context of an existing firm, is generally known as corporate entrepreneurship (CE). CE involves three main activities: Corporate venturing is the creation of organizations within or outside the existing organizational domain (Marchisio et al ); S trategic renewal is organizational renewal involving major strategic and/or structural changes (e.g., Wang et al ); and Innovation is the introduction of something new to the market (e.g., Block et al ). …”
Section: Conceptualizing Entrepreneurship In Family Firmsmentioning
confidence: 99%
“…Corporate venturing is the creation of organizations within or outside the existing organizational domain (Marchisio et al 2010); Strategic renewal is organizational renewal involving major strategic and/or structural changes (e.g., Wang et al 2016); and Innovation is the introduction of something new to the market (e.g., Block et al 2013).…”
Section: Entrepreneurship In Family Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review paper, it is also found some papers that empirically investigate the effect of corporate political connections on business strategy, innovation and R & D intensity. For instance, Wang et al (2016) study how family firms with political connections transform their business and adopt M & a strategy. Linking political connections and corporate innovation has also been studied by some papers not only in management field (Song et al, 2015) but also in corporate finance (Hou et al, 2017).…”
Section: Business Strategy Innovation and Randd Intensitymentioning
confidence: 99%
“…In the search for a valid instrument we aim to find an exogenous variable that is economically correlated with the political connections variable but not with financial policies. In the spirit of earlier studies such as Ferris et al, (2016) and Wang et al (2016) the extent of political connections in the connected firm's industry (Indus_connection) is taken as a discerning instrumental variable for political connections. Specifically, it is defined as the number of connected firms in a given industry divided by the total number of firms in that industry.…”
Section: Capital Structurementioning
confidence: 99%